Exploring the utility of exposure therapy in anorexia nervosa: the role of the fear of food measure - Kulish, Bailee, author; Chavez, Ernest, advisor; Emery, Noah, committee member; Dik, Bryan, committee member; Faw, Meara H., committee member (Colorado State University. Libraries, 2025)
Background: Approximately 5% of patients diagnosed with anorexia nervosa (AN) die within four years of the diagnosis (Crisp et al., 1992; Moller-Madsen et al., 1970–1987; Patton, 1988). However, current evidence-based treatments for AN show limited efficacy (e.g., McIntosh et al., 2005; Kaidesoja et al., 2023). Exposure therapies have been recommended for use in AN due to the extensive overlap of anxiety disorder and eating disorder (ED) symptoms (e.g., Strober et al., 2004; Steinglass & Walsh, 2006), though which anxieties are central to ED symptomology is understudied (e.g., fear of weight gain, Brown & Levinson, 2022; Fairburn et al., 2009; fear of food, Brown & Levinson, 2022; Steinglass et al., 2010). The Fear of Food Measure (FOFM) examines fears that address all three components of a cognitive-behavioral model of anxiety. This study will examine the efficacy of exposure therapy in AN by examining scores on the FOFM and ED outcomes (using the Eating Disorder Inventory-3 (EDI-3)) after exposure therapy interventions. It will also examine the validity of fear of food (using the FOFM) as a central motivator/component to AN, by examining the connection between scores on the FOFM and the EDI-3. Lastly, this study will examine weight gain and its relationship to the FOFM and EDI-3. Results: Scores on the subscales of the FOFM and the EDI-3 significantly decreased from pre- to post-treatment. Feared Concerns was a significant predictor of all EDI-3 subscales, while Food Anxiety Behaviors was not. Additionally, Anxiety about Eating subscale significantly predicted some of the EDI-3 subscales, including Drive for Thinness and Body Dissatisfaction. Lastly, subscales on the FOFM were not a significant predictor of weight gain during treatment. Weight gain was also not a significant predictor of decreased scores on the EDI-3 subscales at post-treatment, aside from Drive for Thinness, although post analysis showed significant weight gain among participants from pre- to post-treatment.
Keywords: eating disorders; fear of food measure; anorexia nervosa; meal therapy; exposure therapy